PERCEIVED QUALITY OF LIFE AND SOCIAL SUPPORT RECEIVED BY THE ELDERLY IN IBADAN NORTH LOCAL GOVERNMENT AREA, OYO STATE, NIGERIA (2014)
The elderly (people aged 65years and above) constitute over 3% of the Nigerian population. The increasing number and vulnerability to numerous geriatric health and social problems associated with this age group make their well-being and Quality Of Life (QOL) an important issue. However, few studies exist on social support and the different aspects of QOL among the elderly in Nigeria. This study was therefore designed to explore the perceived QOL and social support received by the elderly in Ibadan North Local Government Area, Oyo State, Nigeria. A descriptive cross-sectional design was adopted. Twenty communities were randomly selected and 613 respondents were selected using the purposive sampling technique. Data were collected using an interviewer administered semi-structured questionnaire. The questionnaire included a 68-point perceived QOL. Questions on physical and psychological health, level of independence and social relationship/environment were included. Scores of 0-34, 35-50 and 51-68 were rated poor, moderate and good QOL respectively. Questions relating to the role of children, family and community were also asked on social support. Six Focus Group Discussion (FGD) sessions were conducted. Data were analysed using descriptive statistics and Chi-square and independent t-test at 0.05 level of significance, while thematic approach was used to analyse FGD data. Respondents’ mean age was 70.7±5.6years, 53.3% were females and 83.5% were Yoruba. About half (55.8%) of the respondents belonged to nuclear families. Almost all (98.9%) had children and of these, 81.8% had children who visit them regularly. Few (6.2%) of the respondents lived alone while 81.6% lived with their families. Those from nuclear families (55.8%) significantly received more social support than those from extended families (44.2%). Few respondents (5.7%) had poor QOL, 47.5% had moderate QOL and 46.8% had good QOL. Concerning physical health domain, 54.3% felt physical pains, 55.6% did not perform exercises regularly and 43.2% had problems with sleeping well. As regards psychological health, 65.6% felt their life was meaningful and 48.9% reported that they sometimes had negative feelings like anxiety and depression. On level of independence, 44.7% reported that age had reduced their ability to perform daily living activities and 42.7% depended a little on medicinal aids to live a normal life. Concerning the social relationship/environment domain, 63.9% reported that they enjoyed life very much and 50.1% got the emotional support they needed from their families. There was significant difference in QOL between those who lived with people (93.8%) compared with those who lived alone while there was significant difference in QOL between those who had children and those who had none. Majority of the FGD discussants expressed their view on the positive impact of social support which added more quality to lives and also made life worth living. Social support enhanced the quality of life of the elderly. Health education strategies such as advocacy and awareness programmes on the relevance of social support especially family support should be developed to enhance the quality of life of the elderly